Contagious migration: Evidence from the Philippines - Michael Ralph M. Abrigo; Desiree A. Desierto (University of the Philippines, School of Economics (UPSE), 2011)
Outward migration data from the Philippines exhibit spatial clustering. This is likely due to information spillover effects-fellow migrants share information with other neighboring migrants, thereby lowering the costs of migration. To verify this, we use spatial econometrics to define a geography-based network of migrants and estimate its effect on the growth in the number of succeeding migrants. We find that current and past migration from one municipality induces contemporaneous and future migration in neighboring municipalities, even while controlling for demographic, economic and institutional factors that may be common across municipalities.
Keywords: C21; D85; F22; 330; Migration; Network effects; Spatial econometrics; Auswanderung; Soziale Beziehungen; Migranten; Informationsverbreitung; Spillover-Effekt; Philippinen